2021
DOI: 10.1038/s41598-021-88971-5
|View full text |Cite
|
Sign up to set email alerts
|

Light quality and quantity affect graft union formation of tomato plants

Abstract: It is already known that there are many factors responsible for the successful formation of a graft union. However, the role of light has been little studied. In an anatomical study, Scanning Electronic Microscope (SEM) was used to explore the effects of different light-emitting diodes (LEDs) on graft union formation in grafted tomato. In addition, the expression genes related to Auxin hormone signaling pathway (SAUR67, AUX1, ARF30, and LAX3) was investigated. The obtained results showed that the concrescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…The expression pattern of Eucgr.A00514 (auxin transporter-like protein 4, LAX4) was downregulated in mat-callus compared to pri-callus in the two Eucalyptus species (additional file 1 ). It is consistent with the discovery of LAX3 gene in rice after grafting [ 32 ]. The dysregulation of these genes may suggest that they might play an essential role from the beginning of wounding to encourage healing and preparation for downstream rapid development.…”
Section: Resultssupporting
confidence: 92%
“…The expression pattern of Eucgr.A00514 (auxin transporter-like protein 4, LAX4) was downregulated in mat-callus compared to pri-callus in the two Eucalyptus species (additional file 1 ). It is consistent with the discovery of LAX3 gene in rice after grafting [ 32 ]. The dysregulation of these genes may suggest that they might play an essential role from the beginning of wounding to encourage healing and preparation for downstream rapid development.…”
Section: Resultssupporting
confidence: 92%
“…Naznin, et al 38 and Yang, et al 39 investigated in pepper seedlings and Yang et al 40 tomato seedlings, and they found that in particular the red LED light was important for producing strong seedlings. Also, Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings 28 , 29 . In most studies a combination of R and B light was more effective in promoting plant growth and development than the use of one LED source alone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that different color ratios (different light spectrums) strongly influence on plants’ physiological and developmental outcomes 21 24 . Other researches revealed the effect of light irradiance on plant growth and development 23 , 25 29 and photoperiod 23 , 30 . However, little is known about the combined effect of light irradiance, quality, and photoperiod on plants’ growth, development, and physiological response.…”
Section: Introductionmentioning
confidence: 99%
“…The major sites of damage owing to high temperature have been identified as carbon metabolism in the stroma and chemical signalling in thylakoid lamellae 12 . Photosynthesis is more heat sensitive as compared to dark respiration and is inhibited before the inhibition of respiration due to the plant's injury caused by high temperature 13 , 14 . High temperature makes plant tissues lose water, which makes it hard for minerals to get where they need to go 15 19 .…”
Section: Introductionmentioning
confidence: 99%